Identifikasi Penyakit Akibat Kerja pada Nelayan di Gampong Lampulo Kecamatan Kuta Alam Kota Banda Aceh Tahun 2025 - Nazira Aklia; Asnawi Abdullah; Tiara Mairani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Fishermen are a group of workers at high risk of developing occupational diseases (OCD) due to exposure to extreme weather, heavy physical activity, non-ergonomic working positions, and limited implementation of occupational safety and health (K3). This study aims to analyze the risks and factors associated with Occupational Occupational Diseases (OCD) among fishermen in Gampong Lampulo, Banda Aceh City. This study used a quantitative method with a cross-sectional design. The study population was 450 fishermen working on vessels measuring 6–10 GT, with a sample of 82 respondents selected using a purposive sampling technique. Data were collected using a questionnaire administered to respondents, and then analyzed using the Chi-Square test at a 95% confidence level. The results showed that 53 respondents (65%) experienced Occupational Diseases (OCD). The most common type of OCD was muscle pain (49%), followed by dermatitis (26%), and work-related injuries (24%). Bivariate analysis results showed that length of service (p=0.028), knowledge (p=0.016), and personal hygiene (p=0.017) were significantly associated with the incidence of PAK in fishermen. Meanwhile, age did not show a significant association with PAK (p=0.086). This study concluded that longer service periods, low levels of knowledge, and poor personal hygiene can increase the risk of PAK in fishermen. Therefore, efforts are needed to improve occupational health and safety education, foster clean and healthy lifestyles, and strengthen occupational health programs to reduce the risk of PAK in fishermen.